EVALUASI SALURAN ISAP DEBU UNTUK SISTEM DUST COLLECTOR - Destyandra Hermanu Ariandi; Endri Kusuma George; Moballa Burniadi (Proceedings Conference on Marine Engineering and its Application, 2018)
In the process of loading and unloading low calorie coal / LRC (Low Range Calorie) there is often pollution of coal dust and self combustion. This is because of the character of LRC coal is easily destroyed, the dust is very light and easy to burn. To prevent the occurrence of fire hazard, it is attempted to break one of the danger chain by optimizing the dust collector. Therefore, the capability of suction dust collector should be increased so that the impact of dust can be reduced. The simulation shows that the dust inside the conveyor can not be inhaled because the velocity of the inlet conveyor is 2.9 m/s. While the suction collector force of 1.5 m/s causes the dust collector not to capture the dust completely. Therefore it is necessary to increase the velocity of the suction channel on the dust collector, by varying with ratios 3 and 4. Between the two variations the best suction is the ratio 3 with the suction rate of 9 m/s. Furthermore, there is a change in suction hood angle with angle variation of 14 degree, 17 degree, 20 degree to get mass concentration. All angle variation within suction speed 12 m/s. The simulation result with an angle of 14 degrees obtained mass concentration of 14940,23 mg/m,3 with an angle of 17 degrees of 3,05 mg/m3, and with an angle of 20 degrees of 0,000741 mg/m3. Of the three variations, the mass concentration obtained at the outlet is at least 20 degrees suction hood angle.